2016
DOI: 10.15619/nzjp/44.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of undertaking a clinical trial using bubble-PEP in an acute exacerbation of chronic obstructive pulmonary disease: A feasibility study

Abstract: The aims of this study were to compare the effect of bubble-positive expiratory pressure with a commercial positive expiratory pressure device and standardised physiotherapy in patients with an acute exacerbation of chronic obstructive pulmonary disease, and to assess the feasibility of inpatient research methods. Patients admitted to a medical ward at Middlemore Hospital, Auckland, New Zealand, with an acute exacerbation of chronic obstructive pulmonary disease were randomly assigned to a treatment group. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Most frequent timings to begin intervention were 24-48 h after hospital admission (n=10) [22,30,31,40,41,45,46,49,53,57], after hospital discharge (n=5) [28,33,35,38,56], at the moment of hospital discharge (n=4) [18,19,36,47] and at hospital admission (n=3) [25,43,55]. [27,45,46,53], positive expiratory pressure therapy performed with noninvasive ventilation [22,54] or devices (n=3) [49], home diaries (n=2) [35,36], respiratory muscle training (n=1) [37], nutrition (n=1) [28] and whole body vibration (n=1) [30]. Only 16 (38.1%) of the included studies [18, 21-24, 26, 28, 29, 31, 34, 35, 38, 39, 44, 46, 56] used pulmonary rehabilitation as an intervention if the pulmonary rehabilitation definition is taken into account [4].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most frequent timings to begin intervention were 24-48 h after hospital admission (n=10) [22,30,31,40,41,45,46,49,53,57], after hospital discharge (n=5) [28,33,35,38,56], at the moment of hospital discharge (n=4) [18,19,36,47] and at hospital admission (n=3) [25,43,55]. [27,45,46,53], positive expiratory pressure therapy performed with noninvasive ventilation [22,54] or devices (n=3) [49], home diaries (n=2) [35,36], respiratory muscle training (n=1) [37], nutrition (n=1) [28] and whole body vibration (n=1) [30]. Only 16 (38.1%) of the included studies [18, 21-24, 26, 28, 29, 31, 34, 35, 38, 39, 44, 46, 56] used pulmonary rehabilitation as an intervention if the pulmonary rehabilitation definition is taken into account [4].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Aerobic training was prescribed at 40-85% of the maximal or submaximal test result [24, 31-33, 37, 40, 44] and strength training at 40-80% of 1-repetition maximum [24,26,40,43,44]. Additional components used were: electrostimulation, which was applied using a range of frequencies from 12-50 Hz [27,30,45,53], with 50 Hz being the most used frequency; positive expiratory pressure therapy which was performed using 10-20 cmH 2 O [22,49]; and respiratory muscle training which was set at 50% of maximal inspiratory pressure [37].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Bottle-PEP is easily assembled by a physician and can be administered as an alternative to commercially available devices, therefore, constituting a valuable choice. [ 20 ] Previous surveys among physical therapists showed that it was used daily in a variety of situations. [ 21 ] A recent review demonstrated that there were only seven articles that implemented bottle-PEP, and most of the existing literature was about the technical properties of the device rather than long-term results.…”
Section: Discussionmentioning
confidence: 99%
“…2016. Most studies were randomized control trials (n = 31) 15,16, conducted with inpatients (n = 27), 15,16,29,30,33,35,[37][38][39][40][41]43,[45][46][47][48][51][52][53][54][55][56][57][58][59][60][61] followed by hospital outpatient departments (n = 6), 15,37,38,42,44,49 inpatients plus patients' homes (n = 3), 31,32,50 community settings (n = 3), 34,62,63 and patients' homes (n = 1) 36 (Tabs. 1 and 2).…”
Section: Phase 1: Measures Used In Pulmonary Rehabilitationmentioning
confidence: 99%